An Integrated Computational–Experimental Hierarchical Approach for the Rational Design of an IL/UiO‐66 Composite Offering Infinite CO2 Selectivity. (26th June 2022) - Zeeshan, Muhammad; Gulbalkan, Hasan Can; Durak, Ozce; Haslak, Zeynep Pinar; Unal, Ugur; Keskin, Seda; Uzun, Alper
Abstract: Owing to the possibility of generating theoretically unlimited numbers of ionic liquid (IL)–metal‐organic framework (MOF) combinations, experimental studies on IL/MOF composites for gas separation applications are mostly conducted on a trial‐and‐error basis. To address this problem, an integrated computational–experimental hierarchical approach is presented for selecting the best IL‐MOF combination for a target gas separation application. For this purpose, UiO‐66 and pyrrolidinium‐based ILs are chosen as the parent MOF and IL family, respectively, and three powerful computational tools, Conductor‐like Screening Model for Realistic Solvents calculations, density functional theory calculations, and grand canonical Monte Carlo simulations, are integrated to identify the most promising IL‐UiO‐66 combination as 1‐ n ‐butyl‐1‐methylpyrrolidinium dicyanamide/UiO‐66, [BMPyrr][DCA]/UiO‐66. Then, this composite is synthesized, characterized in deep detail, and tested for CO2 /N2, CO2 /CH4, and CH4 /N2 separations. Results demonstrate that [BMPyrr][DCA]/UiO‐66 offers an extraordinary gas separation performance, with practically infinite CO2 and CH4 selectivities over N2 at 15 °C and at low pressures. The integrated hierarchical approach proposed in this work paves the way for the rational design and development of novel IL/MOF composites offering exceptional performance for any desired gas separation application. Abstract : An integrated computational–experimental hierarchical approach is presented for selecting the best IL‐MOF combination for extraordinarily high CO2 separation performance. Results demonstrate that [BMPyrr][DCA]/UiO‐66 composite has practically infinite CO2 and CH4 selectivities over N2 at 15 °C and low pressures. The proposed integrated hierarchical approach paves the way for the rational design and development of novel IL/MOF composites.